Bond behaviour between textile reinforcement and mortar under tensile loading / Verbundverhalten zwischen textiler Bewehrung und Mörtel unter Zugbeanspruchung. Issue 4 (August 2016) - Saenger, Dorothea; Brameshuber, Wolfgang
Abstract: Extensive experimental investigations are currently being carried out on various selected materials covering a wide range of properties to achieve a deeper knowledge about the bond performance of textile reinforced mortar (TRM) for masonry strengthening. The objective of the tests includes investigations of the bonding behaviour between alkali‐resistant glass textile reinforcement and mortar under tensile loading to determine the required anchorage and overlapping lengths of the reinforcement in the mortar‐based material. This article describes the test methods used as well as the results obtained so far. This research will also examine debonding of the mortar‐based reinforcement system and the masonry surface under shear load. The definition of these bond parameters is necessary for the design of textile‐reinforced masonry components, which will be developed in the near future. The research is also intended to contribute to the finding or even designing of matching alkali‐resistant glass textiles specifically for use in masonry.